Financing Patterns of Russian Innovative Enterprises: Empirical Evidence - O. N. Korableva; A. Maarouf (Финансы: теория и практика)
Different financial resources are used to finance the operational and innovative activities of enterprises, forming the structure of their capital. Many studies have been conducted on the topic of businesses’ access to external financial resources, such as loans. However, the topic of the relationship of financing patterns with the results of innovation activity and the innovative potential of enterprises is still insufficiently studied. The aim of this article is to identify patterns of financing Russian enterprises, as well as the specifics of financing innovative enterprises. As the main research method, we used cluster analysis, which was conducted for two groups of Russian enterprises — large and small and mediumsized (SMEs) businesses. The study is based on data from a survey of Russian companies conducted by the World Bank. The results show that large enterprises use five financial patterns: equity, trading, loans, mixed financing, and government subsidies. SMEs, on the contrary, are limited to the first four patterns. Special attention was paid to innovative companies, among which most large enterprises rely on their own funds as the main source of financing. At the same time, small and medium-sized innovative enterprises demonstrate a more flexible financial strategy, using a wider range of sources to ensure their innovation activities. The data obtained is of great importance for the development of effective tools to support innovation. Taking into account the identified features of the financial structure of companies, it is necessary to develop measures aimed at stimulating innovation, taking into account the specifics of various types of enterprises. This will not only increase the innovative potential of Russian companies, but also strengthen their positions in the domestic and global markets.